ARSITEK DAN ARSITEKTUR LANSEKAP: SUATU KONTRIBUSI KEPADA BUMI - Mardiana, Riskha (TERAS)
Landscape aspect on architecture field is one of environment creation which important and essential. The beginning of landscape architecture creation is set up from little housing garden until urban and regional planning, designing, and development. All of them are connecting to landscape factor. Landscape just not visual beauty and esthetic only, but included value of life and bring in cultural value. So landscape is architectural aspect that gives inspiration to individual awareness and human existent in the world. Landscape Architect is creative actor that effort to make a quality environment and value life. However, Landscape Architect is contributor to preservation of earth and environment where place of human life.Â